2D-Shear Wave Elastography Increases the Diagnostic Accuracy of the TIRADS-ACR and ATA Classification Systems in Thyroid Nodule Selection: Cytological and Histological Correlation - Moraes, Pedro Henrique; Chammas, Maria Cristina; Vanderlei, Felipe Brasileiro; Schelini, Marcelo Violi; Milani, Carolina De Marqui; Chacon, Danielle Azevedo (Ultraschall in der Medizin - European Journal of Ultrasound, 2025)
The aim was to evaluate whether elastography changes the accuracy of thyroid nodule malignancy risk classification using the TI-RADS ACR and ATA systems.This was a prospective study with 191 nodules (180 patients). Nodule assessments by B-mode ultrasonography (US) and 2-dimensional shear wave elastography (2D-SWE) were compared with a) fine-needle aspiration biopsy cytological (Bethesda II) and b) post-resection histology results (Bethesda III–VI). Nodules were divided into benign and malignant. B-mode US evaluated echogenicity, composition, dimensions, contours, limits, and presence of halo and echogenic foci. Elastography classified nodules from I (completely softened) to IV (completely hard). The mean nodule deformation value (assessed in m/s and kPa), the deformation ratio between nodule and thyroid parenchyma (TDR), and the deformation ratio between nodule and pre-thyroid musculature (MDR) were calculated.The significant univariate parameters for B-mode were hypoechogenicity, halo, microcalcifications, irregular contours, and ill-defined limits. All parameters were significant for elastography. The MDR (in kPa) was the best elastographic parameter: nodules with MDRs> 1.53 exhibited a higher chance of malignancy (AUC-ROC=0.831). B-mode ACR-TIRADS had an AUC of 0.678; 95% CI: 0.596–0.760, while ATA had an AUC of 0.680; 95%: 0.597–0.763. Multivariable analysis indicated that the combination of prognostic models with any elastographic parameter increased performance. ATA classification, combined with elastogram pattern and MDR (in kPa), increased the AUC to 0.892; 95% IC: 0.845–0.939.2D-SWE can increase the accuracy of the most widespread B-mode prognostic models: TI-RADS ACR and ATA.
Keywords: thyroid; ultrasound; ACR TI-RADS (American College of Radiology Thyroid Imaging Reporting and Data System); thyroid nodules; shear wave elastography